Zikir dalam Perspektif Buddha dan Islam - Tri Anggraini; Poniman Poniman; Tejo Ismoyo; Widiyanto Widiyanto (STAIN Bengkalis, 2022)
Zikir is one of the methods used by sufi scholars to be able to revive the heart from death because a heart that does not remember the majesty of Allah is considered dead by the sufis. However, the perspective of zikir in Buddhism is still little known by the public. This lack of understanding shows that the term zikir in Buddhism is still a bit foreign so that many people, especially Buddhists, do not understand the perspective of zikir itself. The purpose of writing this article is to find out about zikir from a Buddhist and Islam perspective. This study used a descriptive qualitative method. Based on the data analysis carried out, it was concluded that zikir is reciting the name of Allah and praying with concentration or ritual verbal worship, which is not tied to time, place or circumstances, and if humans are busy doing it, zikir produces knowledge and vision in themselves, because zikir in its basic context is included in the verbal category. The perspective of zikir in Buddhism (Theravada) is similar to that of sufi meditation in Islamic religion. The difference is only in the form activity and the naming of the training terms. The difference between the two lies in the prescribed meditation subject.